Engineering a Robust DNA Circuit for the Direct Detection of Biomolecular Interactions - Yan Shan, Ang.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book provides essential insights into designing a localized DNA circuit to promote the rate of desired hybridization reactions over undesired leak reactions in the bulk solution. The area of dynamic DNA nanotechnology, or DNA circuits, holds great promise as a highly programmable toolbox that can be used in various applications, including molecular computing and biomolecular detection. However, a key bottleneck is the recurring issue of circuit leakage. The assembly of the localized circuit is dynamically driven by the recognition of biomolecules - a different approach from most methods, which are based on a static DNA origami assembly. The design guidelines for individual reaction modules presented here, which focus on minimizing circuit leakage, are established through NUPACK simulation and tested experimentally - which will be useful for researchers interested in adapting the concepts for other contexts. In the closing section, the design concepts are successfully applied to the biomolecular sensing of a broad range of targets including the single nucleotide mutations, proteins, and cell surface receptors. .
Introduction -- Literature Review -- Materials and Methods -- Modular Framework for Engineering a Self-Contained DNA Circuit -- Designing Hybridization Chain Reaction Monomers for Robust Signal Amplification -- Design Concepts in Association Toehold for Robust Signal Transduction -- DNA Split Proximity Circuit as a General Platform for Interrogating Biomolecular Events -- DNA Split Proximity Circuit for Visualizing Cell Surface Receptor Clustering- A Case Study Using Human Epidermal Growth Factor Receptor Family -- Conclusion and Future Outlooks.
Keywords: Biotechnology; Bioinformatics; Microtechnology; Microelectromechanical systems; Chemical Bioengineering; Computational and Systems Biology; Microsystems and MEMS